Study of the Discrepancies between Crystallographic Porosity and Guest Access into Cadmium–Imidazolate Frameworks and Tunable Luminescence Properties by Incorporation of Lanthanides. Issue 20 (1st April 2016) - Mondal, Suvendu Sekhar; Bhunia, Asamanjoy; Attallah, Ahmed G.; Matthes, Philipp R.; Kelling, Alexandra; Schilde, Uwe; Müller‐Buschbaum, Klaus; Krause‐Rehberg, Reinhard; Janiak, Christoph; Holdt, Hans‐Jürgen
Abstract: An extended member of the isoreticular family of metal–imidazolate framework structures, IFP‐6 (IFP=imidazolate framework Potsdam), based on cadmium metal and an in situ functionalized 2‐methylimidazolate‐4‐amide‐5‐imidate linker is reported. A porous 3D framework with 1D hexagonal channels with accessible pore windows of 0.52 nm has been synthesized by using an ionic liquid (IL) linker precursor. IFP‐6 shows significant gas uptake capacity only for CO2 and CH4 at elevated pressure, whereas it does not adsorb N2, H2, and CH4 under atmospheric conditions. IFP‐6 is assumed to deteriorate at the outside of the material during the activation process. This closing of the metal–organic framework (MOF) pores is proven by positron annihilation lifetime spectroscopy (PALS), which revealed inherent crystal defects. PALS results support the conservation of the inner pores of IFP‐6. IFP‐6 has also been successfully loaded with luminescent trivalent lanthanide ions (Ln III =Tb, Eu, and Sm) in a bottom‐up one‐pot reaction through the in situ generation of the linker ligand and in situ incorporation of photoluminescent Ln ions into the constituting network. The results of photoluminescence investigations and powder XRD provide evidence that the Ln ions are not doped as connectivity centers into the frameworks, but are instead located within the pores of the MOFs. Under UV light irradiation, Tb@IFP‐6 and Eu@IFP‐6 ( λ exc =365 nm) exhibit observable emission changes to a greenish and reddish color, respectively, as a result of strong Ln 4 f emissions. Abstract : Gas admission : Due to the instability of the pentacoordinated cadmium center of activated IFP‐6, the amorphous material and rough surface can be generated by partial framework cleavage at the outer surface, which closes pore windows and results in inherent crystal defects (see figure). At atmospheric pressure, gas molecules probably do not diffuse due to blockages, whereas at high pressure gases are compelled to diffuse into the pores.